The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1742-6723.2006.00928.x
|View full text |Cite|
|
Sign up to set email alerts
|

Commercial aviation in‐flight emergencies and the physician

Abstract: Commercial aviation in-flight emergencies are relatively common, so it is likely that a doctor travelling frequently by air will receive a call for help at some stage in their career. These events are stressful, even for experienced physicians. The present paper reviews what is known about the incidence and types of in-flight emergencies that are likely to be encountered, the international regulations governing medical kits and drugs, and the liability, fitness and indemnity issues facing 'Good Samaritan' medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 19 publications
1
43
0
8
Order By: Relevance
“…The Aviation Medical Assistance Act was passed in the USA in 1988 consequential to the reluctance of doctors to offer assistance for fear of litigation. 4 This Act has a Good Samaritan provision which protects an American physicianpassenger unless they are guilty of gross negligence or willful misconduct (on US registered aircraft only). 1 This provision does not apply if spontaneous medical assistance is given.…”
Section: Medico-legal Issuesmentioning
confidence: 99%
“…The Aviation Medical Assistance Act was passed in the USA in 1988 consequential to the reluctance of doctors to offer assistance for fear of litigation. 4 This Act has a Good Samaritan provision which protects an American physicianpassenger unless they are guilty of gross negligence or willful misconduct (on US registered aircraft only). 1 This provision does not apply if spontaneous medical assistance is given.…”
Section: Medico-legal Issuesmentioning
confidence: 99%
“…One medical incident is estimated to occur for every 10 000 to 40 000 passengers on intercontinental flights (5). Assuming the lower figure and assuming that there are 400 passengers on board each flight, one can calculate that with 95% probability one medical incident will be experienced within 24 intercontinental flights.…”
Section: Medical Incidents On Board: Facts and Figuresmentioning
confidence: 99%
“…They discuss cabin environment as a consideration in responding to in-fl ight medical emergencies, and correlate cabin altitude pressure with the effects of hypoxia and gas expansion. Quoting Schesser, they state " At cruising altitude, the cabin pressure is set to 5,000 to 8,000 feet above mean sea level, rendering all passengers a degree of hypoxia, which can have serious effects on an already sick person " ( 6 ). This in-fl ight emergency pattern was confi rmed by Gendreau and DeJohn, who also found that in many passengers with cardiopulmonary disease oxygen saturation may fall dramatically at ordinary cabin pressures, resulting in hypobaric hypoxia ( 19 ).…”
Section: Review Articlesmentioning
confidence: 99%